Seni Mendeteksi Penyakit Melalui Lidah Dalam Budaya Pengobatan Tradisional Tiongkok - Sinarsari, Ni Made; Sutana, I Gede (Institut Hindu Dharma Negeri Denpasar, 2021)
Traditional medicine is closely related to the culture in which it develops. The art of detecting disease through the tongue is one of the main diagnostic methods in Traditional Chinese Medicine culture that has been applied since the classical times of the Yellow Emperor. Tongue diagnosis in Traditional Chinese Medicine culture is a method for diagnosing disease and disease patterns by visual inspection of the tongue and its various features. As with other diagnostic methods, the diagnosis of the tongue is based on the principle that the outside of the body reflects the inside of the body. The tongue provides important clues that reflect the condition of the internal organs in each patient. In Traditional Chinese Medicine culture, the external structure of the body often reflects the condition of the inner structure and can give an important indication of internal disharmony.